The impact of virtual reality on programming algorithm courses on student learning outcomes - Dewi, Ika Parma; Ambiyar; Effendi, Hansi; Giatman, Muhammad; Hanafi, Hafizul Fahri; Ali, Siti Khadijah (Society for Research and Knowledge Management, 2024)
The low learning outcomes of students and the limitations of learning media provide opportunities to develop innovations that can increase student engagement. One form of innovative and interactive media that supports student engagement is VR technology. This study aims to determine the impact of VR compared to traditional learning in improving student learning outcomes on programming algorithm materials. The method applied was a quasi-experimental design through pretest and posttest. The population in this study consists of six classes. Through random sampling techniques, class A was selected as the control class with 19 students and class B as the experimental class with 16 students. In the control class, students apply traditional learning, while the experimental class uses VR-based learning. The data was processed with the Wilcoxon test to see the improvement of learning outcomes in each class and the Mann-Whitney test to compare results in both classes. The results of the Wilcoxon test showed a score of sig (2tailed)<0.05 in both classes which showed that traditional learning and learning with VR encouraged improved student learning outcomes. Traditional learning scores increased from 53 to 67, while group scores. Meanwhile, the results of the Mann-Whitney test showed a score of sig (2tailed)<0.05 which means that the effectiveness of VR is better in improving learning outcomes than traditional learning. Therefore, learning with VR effectively improves student learning outcomes on programming algorithm materials. Other researchers can conduct further research to explore and investigate the impact of VR on health and the use of remote learning.